Research on Optimization of Regional Integrated Energy System Based on Thermal Inertia of Building Clusters. Issue 1 (1st February 2022) - Liu, Xiaodong; Wang, Weiyuan; Zhou, Hengjun; Wu, Gang; Tao, Yongjin
Abstract: With the increase in the share of energy from new energy sources such as photovoltaics and wind power, the development and application of integrated energy systems are becoming more and more rapid. However, if energy is not coordinated and optimized, wind and solar abandonment may occur. This is to achieve a variety of energy sources. The integration, complementarity and flexible regulation of the company have brought great challenges. The fifth-generation district heating and cooling system, as a new direction of comprehensive energy development, can greatly improve the energy efficiency of sources and networks and the convenience of user-side energy consumption, but its adjustment potential for the user-side is insufficient. This paper explores the thermal inertia of the existing infrastructure in the system, that is, the user-side building cluster in the regional thermal system, and uses the thermal inertia of the building cluster to improve the overall potential flexibility of the regional-level integrated energy system and realize the optimized operation of the regional integrated energy system, then improve the flexibility and economy of system operation.